Tantalum capacitor with increased stability
Patent Information
- Application Number
- JP2024208545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-12
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-05
Smart Images

Figure 2025029038000014 
Figure 2025029038000015 
Figure 2025029038000016
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 945,913, filed December 10, 2019, and U.S. Provisional Patent Application No. 62 / 947,014, filed December 12, 2019, which are incorporated by reference in their entireties. [Background technology]
[0002] Tantalum capacitors are typically fabricated by pressing tantalum powder around metal leads, sintering the pressed parts, anodizing the sintered anodes, and then applying a solid electrolyte. Conductive polymers are often used as the solid electrolyte due to their advantageous low equivalent series resistance (ESR) and "non-burning / non-ignition" failure mode. For example, such electrolytes can be formed by in-situ chemical polymerization of 3,4-dioxythiophene monomer (EDOT) in the presence of a catalyst and a dopant. However, conventional capacitors using in-situ polymerized polymers have relatively high leakage currents (DCL) and tend to fail at high voltages such as those experienced during fast switching or operating current spikes. In an attempt to overcome these problems, dispersions formed from a composite of poly(3,4-ethylenedioxythiophene) and poly(styrenesulfonate) (PEDOT:PSS) have also been used. Although PEDOT:PSS dispersions can provide improved leakage current values, other problems nevertheless remain. For example, one problem with polymer slurry-based capacitors is that they can exhibit relatively poor capacitance stability when subjected to repeated voltage charge cycles. Summary of the Invention [Problem to be solved by the invention]
[0003] Therefore, a need exists for improved solid electrolytic capacitors that exhibit relatively stable electrical properties. [Means for solving the problem]
[0004] According to one embodiment of the present invention, a solid electrolytic capacitor is disclosed that includes a capacitor element. The capacitor element includes an anode body including tantalum, a dielectric disposed on the anode body; and a solid electrolyte disposed on the dielectric. The solid electrolyte includes an inherently conductive polymer that includes repeating thiophene units. Additionally, the capacitor exhibits a dielectric strength of about 0.6 volts / nanometer or greater. The capacitor also exhibits a charge / discharge capacitance after being subjected to 3,000 cycles of a surge voltage and an initial capacitance before being subjected to the surge voltage, the ratio of the charge / discharge capacitance to the initial capacitance being about 0.75-1.
[0005] Other features and aspects of the invention are set forth in greater detail below.
[0006] A full and enabling disclosure of the present invention, including the best mode thereof, directed to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, which makes reference to the appended drawings, in which: [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of a capacitor of the assembly of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of another embodiment of a capacitor of the assembly of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of yet another embodiment of a capacitor of the assembly of the present invention. [Figure 4] FIG. 4 is a top view of yet another embodiment of a capacitor of the assembly of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Repeat use of reference characters in the present specification and drawings is intended to represent same or analogous features or components of the invention.
[0009] It will be appreciated by those skilled in the art that this discussion is a description of exemplary embodiments only and is not intended to limit the broader aspects of the invention, which may be embodied in the exemplary configurations.
[0010] Generally speaking, the present invention relates to a solid electrolytic capacitor comprising a capacitor element comprising an anode body comprising tantalum, a dielectric disposed on the anode body, and a solid electrolyte disposed on the dielectric, the solid electrolyte comprising a conductive polymer comprising repeating thiophene units. The inventors have discovered that by selectively controlling certain properties of the capacitor element and the materials from which the capacitor element is formed, capacitors can be formed having a high degree of dielectric strength, thereby improving capacitance stability. "Dielectric strength" generally refers to the ratio of the "breakdown voltage" of a capacitor (the voltage at which the capacitor breaks down, in volts, "V") to the thickness of the dielectric (in nanometers, "nm"). Capacitors typically exhibit a dielectric strength of about 0.6 V / nm or greater, in some embodiments about 0.65 V / nm or greater, in some embodiments about 0.7 V / nm or greater, in some embodiments about 0.75 to about 1 V / nm, and in some embodiments about 0.8 to about 0.9 V / nm. The capacitor may exhibit a relatively high breakdown voltage, for example, about 55 volts or more, in some embodiments about 65 volts or more, in some embodiments about 85 volts or more, in some embodiments about 90 volts or more, in some embodiments about 95 volts or more, and in some embodiments about 100 volts to about 300 volts, as determined by increasing the applied voltage by 3 volts until the leakage current reaches 1 mA. Although the thickness may generally vary depending on the specific location of the anode body, the "dielectric thickness" for purposes of determining the dielectric strength is generally considered to be the maximum thickness of the dielectric, and is usually about 60 nm or more, in some embodiments about 60 to about 500 nm, in some embodiments about 80 to about 350 nm, and in some embodiments about 100 to about 300 nm.
[0011] The resulting capacitor can maintain stable electrical properties (e.g., capacitance) under a wide range of different conditions. For example, the ratio of capacitance (charge and discharge capacitance) after being subjected to repeated cycles of a surge voltage to the initial capacitance value before such testing can be about 0.75 to 1, in some embodiments about 0.8 to 1, in some embodiments about 0.85 to 1, in some embodiments about 0.9 to 1, in some embodiments 0.91 to 0.99, and in some embodiments 0.92 to 0.99. The surge voltage can be applied for 1,000 to 16,000 cycles (e.g., 1,000, 2,000, 3,000, 4,000, 5,000, 8,000, 12,000, or 16,000 cycles). For example, after 3,000 cycles, the capacitor may exhibit a charge / discharge capacitance of 0.75-1, in some embodiments, about 0.95-1, in some embodiments, about 0.96-1, and in some embodiments, about 0.97-1.
[0012] In addition, the capacitance may also be measured by subjecting the material to high temperatures, such as at least about 80° C., in some embodiments from about 100° C. to about 150° C., in some embodiments from about 105° C. to about 130° C. (e.g., 105° C. or 125° C.), for at least about 100 hours, in some embodiments, for at least about 1 It may remain stable even after exposure for a significant period of time, such as from 50 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of capacitance after 3,000 hours of exposure to high temperature (e.g., 105° C.) to the initial capacitance value (e.g., 23° C.) is about 0.7 to 1, in some embodiments about 0.8 to 1, in some embodiments about 0.9 to 1, and in some embodiments about 0.91 to 0.99. The actual capacitance value (dry) may vary, but is typically about 1 millifarad per square centimeter (mF / cm) measured at a frequency of 120 Hz. 2 ) or more, in some embodiments, about 2 mF / cm 2 In some embodiments, the range is about 5 to about 50 mF / cm 2In some embodiments, from about 8 to about 20 mF / cm 2 It is.
[0013] In addition to the above, the capacitors may also exhibit other improved electrical properties. For example, after being subjected to an applied voltage (e.g., 120 volts) for about 30 minutes to about 20 hours, in some embodiments, about 1 hour to about 18 hours, and in some embodiments, about 4 hours to about 16 hours, the capacitors may exhibit a leakage current (DCL) of only about 100 microamps (μA) or less, in some embodiments, about 70 μA or less, and in some embodiments, about 1 to about 50 μA. In particular, the capacitors may exhibit such low DCL values even under dry conditions, as described above. The capacitors may also exhibit a relatively low equivalent series resistance (ESR), such as about 200 milliohms, in some embodiments, less than about 150 milliohms, in some embodiments, about 0.01 to about 125 milliohms, and in some embodiments, about 0.1 to about 100 milliohms, measured at an operating frequency of 100 kHz and a temperature of 23° C. The capacitor may also exhibit such ESR values after exposure to temperatures of about 80° C. or higher, in some embodiments from about 100° C. to about 150° C., and in some embodiments from about 105° C. to about 130° C. (e.g., 105° C. or 125° C.) for a significant period of time, such as about 100 hours or more, and in some embodiments from about 150 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of the ESR of the capacitor after 3,000 hours of exposure to a high temperature (e.g., 105° C.) to the initial ESR value of the capacitor (e.g., at 23° C.) is about 2.0 or less, in some embodiments about 1.5 or less, and in some embodiments 1.0 to about 1.3.
[0014] It is also believed that the dissipation factor of the capacitor can be maintained at a relatively low level. Dissipation factor generally refers to the losses that occur in a capacitor and is usually expressed as a percentage of ideal capacitor performance. For example, the dissipation factor of the present capacitor is typically about 250% or less, in some embodiments about 200% or less, and in some embodiments, about 1% to about 180%, measured at a frequency of 120 Hz.
[0015] Various embodiments of the capacitor will now be described in more detail.
[0016] I. Capacitor element A. Anode body The capacitor element includes an anode including a dielectric formed on an anode body. The anode body may be in the form of a sheet, foil, mesh, pellet, etc. Regardless of its form, the anode body is typically formed from tantalum. In one embodiment, for example, the anode body may be in the form of a pellet formed from tantalum powder. The tantalum powder may be formed from a reduction process in which a tantalum salt (e.g., potassium fluorotantalate (K2TaF7), sodium fluorotantalate (Na2TaF7), tantalum pentachloride (TaCl5), etc.) is reacted with a reducing agent. The reducing agent may be provided in the form of a liquid, gas (e.g., hydrogen), or solid, such as a metal (e.g., sodium), metal alloy, or metal salt. For example, in one embodiment, a tantalum salt (e.g., TaCl5) is heated to about 900° C. to about 2,000° C., In some embodiments, it can be heated at a temperature of about 1,000° C. to about 1,800° C., and in some embodiments, about 1,100° C. to about 1,600° C., to form a vapor, which can be reduced in the presence of a gaseous reducing agent (e.g., hydrogen). Further details of such reduction reactions are described in WO-2014 / 199480 by Maeshima et al. After reduction, the product can be cooled, crushed, and washed to form a powder.
[0017] When used, the specific charge of the powder typically ranges from about 2,000 to about 600,000 microfarad·volts per gram (μF·V / g) depending on the desired application. For example, in some embodiments, high charge powders can be used having a specific charge of about 100,000 to about 600,000 μF·V / g, in some embodiments, about 120,000 to about 500,000 μF·V / g, and in some embodiments, about 150,000 to about 400,000 μF·V / g. In other embodiments, low charge powders can be used having a specific charge of about 2,000 to about 100,000 μF·V / g, in some embodiments, about 5,000 to about 80,000 μF·V / g, and in some embodiments, about 10,000 to about 70,000 μF·V / g. As known in the art, the specific charge can be determined by multiplying the capacitance by the anodization voltage used and then dividing this product by the weight of the anodized electrode body. The powder may be a free-flowing fine powder comprising primary particles. The primary particles of the powder typically have a median diameter (D50) of about 5 to about 500 nanometers, in some embodiments about 10 to about 400 nanometers, and in some embodiments about 20 to about 250 nanometers, as determined using, for example, a laser particle size distribution analyzer (e.g., LS-230) from BECKMAN COULTER Corporation, optionally after subjecting the particles to ultrasonic vibration for 70 seconds. The primary particles typically have a three-dimensional particle shape (e.g., spherical or angular). Such particles typically have a relatively low "aspect ratio," i.e., the average diameter or width of the particle divided by the average thickness (D / T). For example, the aspect ratio of the particles may be about 4 or less, in some embodiments about 3 or less, and in some embodiments about 1 to about 2. In addition to the primary particles, the powder may contain other types of particles, such as secondary particles formed by aggregation (or agglomeration) of the primary particles. Such secondary particles may have a median diameter (D50) of from about 1 to about 500 micrometers, and in some embodiments, from about 10 to about 250 micrometers.
[0018] The particles can be aggregated by heating the particles and / or by using a binder, for example, at a temperature of from about 0° C. to about 40° C., in some embodiments from about 5° C. to about 35° C., and in some embodiments from about 15° C. to about 30° C. Also suitable binders may include, for example, poly(vinyl butyral); poly(vinyl acetate); poly(vinyl alcohol); poly(vinylpyrrolidone); cellulose polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and methylhydroxyethyl cellulose; atactic polypropylene, polyethylene; polyethylene glycols (e.g., Carbowax from Dow Chemical Co.); polystyrene, poly(butadiene / styrene); polyamides, polyimides, and polyacrylamides, high molecular weight polyethers; copolymers of ethylene oxide and propylene oxide; fluoropolymers such as polytetrafluoroethylene, polyvinylidene fluoride, and fluoroolefin copolymers; acrylic polymers such as sodium polyacrylate, poly(lower alkyl acrylates), poly(lower alkyl methacrylates), and copolymers of lower alkyl acrylates and methacrylates; and fatty acids and waxes such as stearic acid and other soap fatty acids, vegetable waxes, microcrystalline waxes (refined paraffins), and the like.
[0019] The resulting powder can be compressed to form pellets using any conventional powder pressing equipment, such as a single station press including a die and one or more punches. A press can be used that is a press. Alternatively, an anvil type compression press can be used that uses only a die and a single lower punch. Single station compression presses are available in several basic types such as cam presses, toggle / knuckle presses, and eccentric / crank presses with various capabilities such as single action, double action, floating die, moving platen, opposed ram, screw, impact, hot pressing, coining, or sizing. The powder can be compressed around the anode lead, which can be in the form of a wire, sheet, or the like. The lead can extend longitudinally from the anode body and can be formed from any conductive material such as tantalum, niobium, aluminum, hafnium, titanium, and the like, as well as conductive oxides and / or nitrides thereof. Connection of the lead to the anode body can also be accomplished using other known techniques, for example, by welding the lead to the anode body or embedding it within the anode body during formation (e.g., prior to compaction and / or sintering).
[0020] The binder can be removed by heating the pellets after pressing under vacuum at a certain temperature (e.g., about 150°C to about 500°C) for several minutes. Alternatively, the binder can be removed by contacting the pellets with an aqueous solution such as that described in U.S. Patent No. 6,197,252 to Bishop et al. The pellets are then sintered to form a porous integral member. The pellets are typically sintered at a temperature of about 700°C to about 1800°C, in some embodiments about 800°C to about 1700°C, in some embodiments about 900°C to about 1400°C, for about 5 minutes to about 100 minutes, in some embodiments about 8 minutes to about 15 minutes. This can be done in one or more steps. If desired, sintering can be done in an atmosphere that limits the migration of oxygen atoms to the anode body. For example, sintering can be done in a reducing or inert atmosphere, such as in a vacuum, in an inert gas, or in hydrogen. The reducing atmosphere may be at a pressure from about 10 Torr to about 2000 Torr, in some embodiments from about 100 Torr to about 1000 Torr, and in some embodiments, from about 100 Torr to about 930 Torr. Mixtures of hydrogen and other gases, such as argon or nitrogen, can also be used.
[0021] B. Dielectric The anode is also coated with a dielectric. As indicated above, the dielectric is formed by anodizing the anode such that a dielectric layer is formed on and / or within the anode. For example, a tantalum (Ta) anode can be anodized to tantalum pentoxide (Ta2O5). Typically, anodization is performed by first applying an electrolyte to the anode, for example by immersing the anode in the electrolyte. The electrolyte is generally in the form of a liquid, such as a solution (e.g., aqueous or non-aqueous), dispersion, or melt. Solvents such as water (e.g., deionized water); ethers (e.g., diethyl ether, tetrahydrofuran); glycols (e.g., ethylene glycol, propylene glycol, and the like); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, and methoxypropyl acetate); amides (e.g., dimethylformamide, dimethylacetamide, dimethylcapryl / capric fatty acid amide, and N-alkylpyrrolidones); nitriles (e.g., acetonitrile, propionitrile, butyronitrile, and benzonitrile); sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane), and the like, are commonly used in electrolytes. The solvent or solvents may comprise from about 50% to about 99.9% by weight of the electrolyte, in some embodiments from about 75% to about 99% by weight, and in some embodiments, from about 80% to about 95% by weight. Although not required, the use of an aqueous solvent (e.g., water) is often desirable to facilitate oxide formation. Indeed, water may comprise at least about 1% by weight, and in some embodiments at least 10% by weight, and in some embodiments at least about It may constitute 50% by weight or more, in some embodiments, about 70% by weight or more, and in some embodiments, about 90% to about 100% by weight.
[0022] The electrolyte is electrically conductive and may have a conductivity of 1 milliSiemens per centimeter (mS / cm) or greater, in some embodiments 30 mS / cm or greater, and in some embodiments, from about 40 mS / cm to about 100 mS / cm, measured at a temperature of 25° C. To increase the conductivity of the electrolyte, ionic compounds that can dissociate in the solvent to form ions are typically used. Suitable ionic compounds for this purpose include, for example, acids such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boronic acid, etc.; carboxylic acids, such as acrylic acid, methacrylic acid, malonic acid, succinic acid, salicylic acid, sulfosalicylic acid, adipic acid, maleic acid, malic acid, oleic acid, gallic acid, tartaric acid, citric acid, formic acid, acetic acid, glycolic acid, oxalic acid, propionic acid, phthalic acid, isophthalic acid, glutaric acid, gluconic acid, lactic acid, aspartic acid, glutamic acid, itaconic acid, trifluoroacetic acid, barbituric acid, cinnamic acid, benzoic acid, 4-hydroxybenzoic acid, Examples of suitable ionic compounds include organic acids such as aminobenzoic acid; sulfonic acids such as methanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, styrenesulfonic acid, naphthalenedisulfonic acid, hydroxybenzenesulfonic acid, dodecylsulfonic acid, dodecylbenzenesulfonic acid, and the like; and polymeric acids such as poly(acrylic) or poly(methacrylic) acids and their copolymers (e.g., maleic-acrylic, sulfonic-acrylic, and styrene-acrylic copolymers), carrageenic acid, carboxymethylcellulose, alginic acid, and the like. The concentration of the ionic compound is selected to achieve the desired conductivity. For example, the acid (e.g., phosphoric acid) may comprise from about 0.01% to about 5% by weight, in some embodiments from about 0.05% to about 0.8% by weight, and in some embodiments from about 0.1% to about 0.5% by weight of the electrolyte. Blends of multiple ionic compounds can also be used in the electrolyte if desired.
[0023] To form the dielectric, a current is typically passed through the electrolyte while it is in contact with the anode body. The value of the formation voltage controls the thickness of the dielectric layer. For example, the power supply can first be set in constant current mode until the required voltage is reached. The power supply can then be switched to potentiostatic mode to ensure that the desired dielectric thickness is formed over the entire surface of the anode. Of course, other known methods such as pulse or step potentiostatic methods can also be used. The voltage at which the anodization is performed is typically in the range of about 4 to about 250 V, in some embodiments about 5 to about 200 V, and in some embodiments about 10 to about 150 V. During oxidation, the electrolyte can be maintained at an elevated temperature, for example, at or above about 30° C., in some embodiments about 40° C. to about 200° C., and in some embodiments about 50° C. to about 100° C. Anodization can also be performed at or below ambient temperature. The resulting dielectric layer can be formed on the surface of the anode and within its pores.
[0024] Although not required, in some embodiments, the dielectric layer can have a differentiated thickness throughout the anode in that it has a first portion disposed on the outer surface of the anode and a second portion disposed on the inner surface of the anode. In such embodiments, the first portion is selectively formed such that its thickness is greater than the thickness of the second portion. However, it should be understood that the thickness of the dielectric layer need not be uniform within a particular region. Some portions of the dielectric layer adjacent to the outer surface, for example, may actually be thinner than some portions of the layer at the inner surface, and vice versa. Nevertheless, the dielectric layer can be formed such that at least a portion of the layer at the outer surface has a greater thickness than at least a portion at the inner surface. While the actual difference in these thicknesses can vary depending on the particular application, the ratio of the thickness of the first portion to the thickness of the second portion is typically about 1.2 to about 40, in some embodiments about 1.5 to about 25, and in some embodiments about 2 to about 20.
[0025] A multi-step process can be used to form dielectric layers having differentiated thicknesses. In each step of the process, a sintered anode is anodized to form a dielectric layer (e.g., tantalum pentoxide). During the first step of anodization, a relatively small formation voltage is typically used to ensure that the desired dielectric thickness is achieved for the interior region, for example, a formation voltage in the range of about 1 to about 90 volts, in some embodiments about 2 to about 50 volts, and in some embodiments about 5 to about 20 volts. The sintered body can then be anodized in a second step of the process to increase the dielectric thickness to a desired level. This is generally accomplished by anodizing in an electrolyte at a formation voltage higher than that used during the first step, for example, a formation voltage in the range of about 50 to about 350 volts, in some embodiments about 60 to about 300 volts, and in some embodiments about 70 to about 200 volts. During the first and / or second stages, the electrolyte may be maintained at a temperature within the range of from about 15°C to about 95°C, in some embodiments from about 20°C to about 90°C, and in some embodiments, from about 25°C to about 85°C.
[0026] The electrolytes used during the first and second stages of the anodization process may be the same or different. However, typically, the electrolyte used during at least one stage of the dielectric growth process comprises an ionic compound as described above. In one particular embodiment, it may be desirable for the electrolyte used in the second stage to have a lower ionic conductivity than the electrolyte used in the first stage, so as to prevent a significant amount of oxide film from forming on the inner surface of the anode. In this regard, the electrolyte used during the first stage may comprise an ionic compound that is an acid, such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boronic acid, and the like. Such electrolytes may have a conductivity, measured at a temperature of 25° C., of about 0.1 to about 100 mS / cm, in some embodiments about 0.2 to about 20 mS / cm, and in some embodiments about 1 to about 10 mS / cm. The electrolyte used during the second stage may also comprise an ionic compound that is a salt of a weak acid, such that the hydronium ion concentration increases in the pores as a result of charge passage therethrough. Ion transport or diffusion occurs such that anions of the weak acid migrate into the pores as needed to balance the charge. As a result, the concentration of the main conductive species (hydronium ions) decreases as an equilibrium is formed between hydronium ions, acid anions, and undissociated acid, forming poorly conductive species. The decrease in the concentration of the conductive species results in a relatively high voltage drop in the electrolyte, which prevents further anodization in the interior, while a thicker oxide layer builds up on the exterior for high formation voltages in the successive high conductivity regions. Suitable weak acid salts can include, for example, ammonium or alkali metal salts (e.g., sodium, potassium, etc.) of boric acid, boronic acid, acetic acid, oxalic acid, lactic acid, adipic acid, and the like. Particularly suitable salts include sodium tetraborate and ammonium pentaborate. Such electrolytes typically have a conductivity of about 0.1 to about 20 mS / cm, in some embodiments about 0.5 to about 10 mS / cm, and in some embodiments about 1 to about 5 mS / cm, measured at a temperature of 25°C.
[0027] If desired, each step of anodization can be repeated for one or more cycles to achieve the desired dielectric thickness. Additionally, the anode can be rinsed or washed with other solvents (e.g., water) after the first and / or second steps to remove the electrolyte.
[0028] C. Precoat If desired, a precoat can be used that is disposed over the dielectric and positioned between the dielectric and the solid electrolyte. The precoat has the following general formula (V):
[0029] [ka]
[0030] (In the formula, Z is an organometallic atom such as silicon or titanium; R1, R2, and R3 are independently alkyl (e.g., methyl, ethyl, propyl, etc.) or hydroxyalkyl (e.g., hydroxymethyl, hydroxyethyl, hydroxypropyl, etc.), and at least one of R1, R2, and R3 is hydroxyalkyl; n is an integer from 0 to 8, in some embodiments from 1 to 6, and in some embodiments from 2 to 4 (e.g., 3); X is an organic or inorganic functional group such as glycidyl, glycidyloxy, mercapto, amino, vinyl, etc. The compounds may include organometallic compounds such as those having the formula:
[0031] In some embodiments, at least one of R1, R2, and R3 in formula (II) can be hydroxyalkyl (e.g., OCH3). For example, each of R1, R2, and R3 can be hydroxyalkyl. However, in other embodiments, R1 can be alkyl (e.g., CH3), and R2 and R3 can be hydroxyalkyl (e.g., OCH3).
[0032] In some embodiments, X may be an amino group. Suitable amino-functional organosilane compounds include, for example, those having the following general formula (II):
[0033] [ka]
[0034] (In the formula, R1, R2, and R3 are as defined above; R4 and R5 are independently hydrogen, alkyl, alkyl, alkenyl, aryl. N, R4, and R5 together with one or more additional atoms form a ring structure (e.g., heteroaryl or heterocyclyl); Z is an organic group that links the nitrogen atom to the silicon atom, such as alkyl (e.g., ethyl or propyl), aryl (e.g., phenyl), etc. Examples of the monoamine functional silanes include those having the formula:
[0035] Examples of monoamino-functional organosilane compounds include, for example, primary amine compounds (e.g., 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltris(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxypropyltrimethoxysilane, aminopropylsilanetriol, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, etc.); secondary amine compounds (e.g., N-butylaminopropyltrimethoxysilane, N-ethylaminoisobutyltrimethoxysilane, etc.); Silane, n-methylaminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, (phenylaminoethyl)methyl-diethoxysilane, N-phenylaminomethytrimethoxysilane, N-methylaminopropylmethyl-dimethoxysilane, etc.; tertiary amine compounds (e.g., bis(2-hydroxyethyl)3-aminopropyltriethoxysilane, diethylaminomethyltriethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, etc.); and combinations thereof. Furthermore, if desired, additional groups may be attached to the nitrogen atom to make the compound a quaternary amine functional silane compound.
[0036] The following general formula (III):
[0037] [ka]
[0038] (In the formula, R1, R2, R3, R4, and R5 are as defined above; Z1 is an organic group that links the nitrogen atom to the silicon atom, and Z2 is an organic group that links the nitrogen atoms together, such as an alkyl (e.g., ethyl or propyl), aryl (e.g., phenyl), etc. Diamino-functional silane compounds may also be used, such as those having the formula: Examples of lanthanide compounds include, for example, N-(2-aminoethyl)-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(6-aminohexyl)aminomethyl-triethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, (aminoethylaminomethyl)-phenethyltrimethoxysilane, N-3-[(amino(polypropyleneoxy)]-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylamino)-3-isobutyldimethylmethoxysilane, and the like, and combinations thereof. Triamino-functional compounds such as (3-trimethoxysilylpropyl)-diethylenetrimamine can also be used.
[0039] Of course, as indicated above, other functional groups may be used. For example, in some embodiments, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2,2-dimethoxy-1-thia-2-silacyclopentane, 11-mercaptoundecyltrimethoxysilane, S-(octanoyl)mercaptopropyltriethoxysilane, 2-(2-pyridylethyl)thiopropyl-trimethoxysilane, 2-(4-pyridylethyl)thiopropyltrimethoxysilane, 3-thiocyanopropyltrimethoxysilane, 2-(3-pyridylethyl)thio ... Sulfur functional silane compounds such as 3-(trimethoxysilylpropylthio)-thiophene, mercaptomethylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis[3-(triethoxysilyl)propyl]tetrasulfide, bis[3-(triethoxysilyl)propyl]disulfide, bis[m-(2-triethoxysilylethyl)tolyl]polysulfide, bis[3-(triethoxysilyl)propyl]thiourea, and the like, and combinations thereof, can be used.
[0040] The particular method of applying the precoat to the capacitor body may vary as desired. In one particular embodiment, the compound is dissolved in an organic solvent and applied as a solution to the component by screen printing, dipping, electrocoating, spraying, or the like. The organic solvent may vary, but is typically an alcohol, such as methanol, ethanol, and the like. The organometallic compound may comprise from about 0.1% to about 10% by weight of the solution, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments from about 0.5% to about 5% by weight. Additionally, the solvent may comprise from about 90% to about 99.9% by weight, in some embodiments from about 92% to about 99.8% by weight, and in some embodiments from about 95% to about 99.5% by weight of the solution. Once applied, the component may then be dried to remove the solvent therefrom to form a precoat layer including the organometallic compound.
[0041] D. Solid electrolyte A solid electrolyte is disposed over the dielectric and any precoat, which typically functions as the cathode for the capacitor. Typically, the total thickness of the solid electrolyte is from about 1 to about 50 μm, and in some embodiments, from about 5 to about 20 μm. Typically, the solid electrolyte comprises an inherently conductive polymer having a positive charge disposed on the backbone that is at least partially compensated by anions covalently bonded to the polymer. For example, one suitable inherently conductive polymer has the following formula (I):
[0042] [ka]
[0043] (In the formula, R is (CH2) a -O-(CH2) b -L, where L is a bond or HC([CH2] c H) is; a is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1); b is 1 to 18, in some embodiments 1 to 10, and in some embodiments 2 to 6 (e.g., 2, 3, 4, or 5); c is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1); M is an anion such as SO3, C(O)O, BF4, CF3SO3, SbF6, N(SO2CF3)2, C4H3O4, ClO4, etc.; X is a cation such as hydrogen, an alkali metal (e.g., lithium, sodium, rubidium, cesium, or potassium), ammonium, etc. The repeating thiophene units may be:
[0044] In one particular embodiment, M in formula (I) represents an intrinsically conductive polymer having the following formula (II):
[0045] [ka]
[0046] wherein R and X are as defined above. In formula (I) or (II), a is preferably 1 and b is preferably 3 or 4. Furthermore, X is preferably sodium or potassium.
[0047] If desired, the polymer may be a copolymer containing other types of repeat units. In such embodiments, the repeat units of formula (V) typically constitute at least about 50 mol %, in some embodiments from about 75 mol % to about 99 mol %, and in some embodiments from about 85 mol % to about 95 mol %, of the total amount of repeat units in the copolymer. Of course, the polymer may be a homopolymer, up to and including 100 mol % of the repeat units of formula (I).
[0048] In another embodiment, the inherently conductive polymer has the following general formula (III):
[0049] [ka]
[0050] (In the formula, a and b are as defined above; R5 is an optionally substituted C1-C6 linear or branched alkyl group (e.g., methyl) or a halogen atom (e.g. fluorine); X is a hydrogen atom, an alkali metal (e.g., Li, Na, or K), NH(R 1 )3(wherein, R 1 are each independently a hydrogen atom or an optionally substituted C1-C6 alkyl group, or HNC5H5. The repeating thiophene units are:
[0051] Specific examples of thiophene compounds used to form such repeating units are described in U.S. Pat. No. 9,718,905, and include, for example, sodium 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl ... -propyl-1-propane-sulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonic acid sodium salt, [3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonic acid sodium salt Sodium oro-1-propanesulfonate, potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate,[4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid triethylammonium, and combinations thereof. Each of the above-exemplified thiophene monomers can be prepared from thieno[3,4-b]-1,4-dioxin-2-methanol and a branched sultone compound by a known method (e.g., Journal of Electroanalytical Chemistry, 443, 217-226 (1998)).
[0052] Intrinsically conductive polymers can be formed by a variety of techniques that will be appreciated by those skilled in the art. In one particular embodiment, for example, thiophene compounds having the general formula (I) can be polymerized in the presence of an oxidation catalyst. Derivatives of these monomers, such as dimers or trimers of the above compounds, can also be used. The derivatives can be composed of the same or different monomer units and can be used in pure form as well as in mixtures with each other and / or with the monomers. The oxidized or reduced forms of these precursors can also be used. The amount of oxidation catalyst used in the polymerization reaction is not particularly limited, but can be in the range of 1 to 50 molar times, more preferably 1 to 20 molar times, relative to the number of moles of thiophene compound used as input material. The oxidation catalyst can be a transition metal salt, such as a salt of an inorganic or organic acid containing ammonium, sodium, gold, iron (III), copper (II), chromium (VI), cerium (IV), manganese (IV), manganese (VII), or ruthenium (III) cations. Particularly suitable transition metal salts include halide, fluorine, fluorine, iod ... halogenides (e.g., FeCl3 or HAuCl4); salts of other inorganic acids (e.g., Fe(ClO4)3, Fe2(SO4)3, (NH4)2S2O8, or Na3Mo 12 PO 40 ); and salts of organic and inorganic acids containing an organic group. Examples of salts of inorganic acids having an organic group include, for example, C1 to C 20 Examples of the salts of organic acids include iron(III) salts of sulfate monoesters of alkanols (e.g., iron(III) salts of lauryl sulfate).20 Iron(III) salts of alkanesulfonic acids (e.g., methane, ethane, propane, butane, or dodecanesulfonic acid); Iron(III) salts of aliphatic perfluorosulfonic acids (e.g., trifluoromethanesulfonic acid, perfluorobutanesulfonic acid, or perfluorooctanesulfonic acid); Iron(III) salts of aliphatic C1-C 20 Iron(III) salts of carboxylic acids (e.g., 2-ethylhexyl carboxylic acid); Iron(III) salts of aliphatic perfluorocarboxylic acids (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C1-C 20 Examples of the iron(III) salt include an aromatic sulfonic acid substituted with an alkyl group (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); an iron(III) salt of a cycloalkanesulfonic acid (e.g., camphorsulfonic acid); etc. Mixtures of the above-mentioned salts may also be used.
[0053] Oxidative polymerization is generally carried out in the presence of one or more solvents. Suitable solvents include, for example, water, glycols (e.g., ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiglycol, dipropylene glycol, etc.); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, isopropyl glycol ether, etc.); alcohols (e.g., methanol, ethanol, n-propanol, iso-propanol, and butanol); ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, methoxypropyl acetate, ethylene carbonate, propylene carbonate, etc.); amides (e.g., dimethylformamide, dimethylacetamide, dimethylcapryl / capric fatty acid amide, and N-alkylpyrrolidone); sulfoxides or sulfones (e.g., dimethylsulfoxide (DMSO) and sulfolane); phenolic compounds (e.g., toluene, xylene, etc.), etc. Water is a particularly suitable solvent for the reaction. The amount of the solvent used in this polymerization reaction is not particularly limited, however, as long as the thiophene compound used as a material is dissolved in the solvent, it is preferably 0.1 to 100 times, more preferably 0.1 to 50 times, the weight of the thiophene compound added. The temperature at which the reaction is carried out usually varies from about -20°C to about 140°C, and in some embodiments, from about 20°C to about 100°C. Once the reaction is complete, any salt impurities can be removed using known purification techniques such as washing with a solvent, reprecipitation, centrifugal sedimentation, ultrafiltration, dialysis, or ion exchange resin treatment, and the like, and combinations thereof.
[0054] Regardless of how it is formed, the polymer is considered to be "intrinsically" conductive so long as it has positive charges located on the backbone that are at least partially compensated by anions covalently bonded to the polymer. The polymer may have a relatively high specific conductivity, for example, in the dry state, of about 1 Siemens per centimeter (S / cm) or more, in some embodiments about 10 S / cm or more, in some embodiments about 25 S / cm or more, in some embodiments about 40 S / cm or more, and in some embodiments about 50 to about 500 S / cm. As a result of its inherent conductivity, the solid electrolyte does not require the addition of traditional dopants such as polystyrene sulfonic acid. In fact, the solid electrolyte may be substantially free of such dopants. It should be understood that dopants may nevertheless be used in certain embodiments of the present invention. However, if utilized, the dopants are typically present in amounts of about 5% by weight or less, and in some embodiments about 2% by weight or less. Hereinafter, in some embodiments, the additive is present in the solid electrolyte in an amount of about 1% by weight or less.
[0055] Polymers are also generally highly soluble in water, which allows them to be applied to the anode more easily and effectively. Soluble polymers can also more easily impregnate the small pores formed by the high specific charge powder, so that the resulting solid electrolyte has a "film-like" structure and substantially uniformly covers at least a portion of the anode. This improves the quality of the resulting oxide as well as its surface coverage, thereby enhancing the electrical properties of the capacitor assembly.
[0056] i. Inner layer The solid electrolyte is generally formed from one or more "inner" conductive polymer layers. The term "inner" in this context refers to one or more layers formed from the same material and overlying the dielectric, either directly or through another layer (e.g., a precoat). For example, the inner layer or layers typically include an intrinsically conductive polymer as described above. In one particular embodiment, the inner layer or layers are generally free of extrinsic conductive polymers and are therefore formed primarily from intrinsically conductive polymers. More specifically, the intrinsically conductive polymer may constitute about 50% or more by weight, in some embodiments about 70% or more by weight, and in some embodiments about 90% or more by weight (e.g., 100% by weight) of the inner layer or layers. One or more inner layers can be used. For example, the solid electrolyte typically includes 2-30, in some embodiments 4-20, and in some embodiments about 5-15 inner layers (e.g., 10 layers).
[0057] The inner layer or layers may be applied in the form of a solution including a solvent. The concentration of polyaniline may vary depending on the desired viscosity and the particular manner in which the layer is applied to the anode. Typically, however, the polyaniline comprises from about 0.1 to about 10 weight percent of the solution, in some embodiments from about 0.4 to about 5 weight percent, and in some embodiments from about 0.5 to about 4 weight percent. Additionally, the solvent or solvents comprise from about 90 weight percent to about 99.9 weight percent of the solution, in some embodiments from about 95 weight percent to about 99.6 weight percent, and in some embodiments from about 96 weight percent to about 99.5 weight percent. If used, the solution may be applied to the anode using any known technique, such as dipping, casting (e.g., curtain coating, spin coating, etc.), printing (e.g., gravure printing, offset printing, screen printing, etc.), and the like. The resulting conductive polymer layer may be dried and / or washed after application to the anode.
[0058] ii. Outer layer The solid electrolyte may include only an "inner layer" such that they are formed from substantially the same material, i.e., an intrinsically conductive polymer. However, in other embodiments, the solid electrolyte may also include one or more optional "outer" conductive polymer layers formed from a different material than the inner layer(s) and disposed on the inner layer(s). For example, the outer layer(s) may be formed from an extrinsic conductive polymer. In one particular embodiment, the outer layer(s) are formed primarily from such extrinsic conductive polymer in that they constitute about 50% or more by weight, in some embodiments about 70% or more by weight, and in some embodiments about 90% or more by weight (e.g., 100% by weight) of the respective outer layer. One or more outer layers may be used. For example, the solid electrolyte may include 2-30, in some embodiments about 4-20, and in some embodiments about 5-15 outer layers.
[0059] When used, the extrinsic conductive polymer may be, for example, a polymer having the following formula (IV):
[0060] [ka]
[0061] (In the formula, R7 is linear or branched C1-C 18 Alkyl groups (e.g., methyl, ethyl, n- or iso-propyl, n-, iso-, sec- or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, etc.); C5 to C 12 Cycloalkyl groups (e.g., cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc.); C6-C 14Aryl groups (e.g., phenyl, naphthyl, etc.); C7-C 18 aralkyl groups (e.g., benzyl, o-, m-, p-tolyl, 2,3-, 2,4-, 2,5-, 2-6-, 3-4-, 3,5-xylyl, mesityl, etc.); C1-C4 hydroxyalkyl groups, or hydroxyl groups; The repeat units may be 0 to 8, in some embodiments an integer from 0 to 2, and in one embodiment 0. In one particular embodiment, "q" is 0 and the polymer is poly(3,4-ethylenedioxythiophene). One commercially suitable example of a monomer suitable for forming such a polymer is 3,4-ethylenedioxythiophene, which is available from Heraeus under the name Clevios™ M.
[0062] The polymers of formula (IV) are generally considered to be "extrinsically" conductive in that they require the presence of another counterion that is not covalently bonded to the polymer. The counterion may be a monomeric or polymeric anion that neutralizes the charge of the conductive polymer. The polymeric anion may be, for example, a polymeric carboxylic acid (e.g., polyacrylic acid, polymethacrylic acid, polymaleic acid, etc.); a polymeric sulfonic acid (e.g., polystyrene sulfonic acid (PSS), polyvinyl sulfonic acid, etc.); and the like. The acid may also be a copolymer, such as a copolymer of vinyl carboxylic acid and vinyl sulfonic acid with other polymerizable monomers, such as acrylic acid esters and styrene. Additionally, suitable monomeric anions include, for example, C1-C 20 Alkanesulfonic acids (e.g., dodecanesulfonic acid); aliphatic perfluorosulfonic acids (e.g., trifluoromethanesulfonic acid, perfluorobutanesulfonic acid, or perfluorooctanesulfonic acid); aliphatic C1-C 20 Carboxylic acids (e.g. 2-ethylhexyl carboxylic acid); aliphatic perfluorocarboxylic acids (e.g. trifluoroacetic acid or perfluorooctanoic acid); optionally C1-C 20Aromatic sulfonic acids substituted by alkyl groups (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); cycloalkanesulfonic acids (e.g., camphorsulfonic acid, Counteranions include anions such as tetrafluoroborate, hexafluorophosphate, perchlorate, hexafluoroantimonate, hexafluoroarsenate, or hexachloroantimonate. Particularly suitable counteranions are polymeric anions such as polymeric carboxylic or sulfonic acids (e.g., polystyrene sulfonic acid (PSS)). The molecular weight of such polymeric anions is typically in the range of about 1,000 to about 2,000,000, and in some embodiments, about 2,000 to about 500,000.
[0063] When used, the exogenous conductive polymer may desirably be applied in the form of a dispersion of prepolymerized conductive particles. Such particles typically have an average dimension (e.g., diameter) of from about 1 to about 100 nanometers, in some embodiments from about 2 to about 80 nanometers, and in some embodiments, from about 4 to about 50 nanometers. The diameter of the particles may be determined using known techniques such as ultracentrifugation, laser diffraction, and the like. The shape of the particles may also vary. In one particular embodiment, for example, the particles are spherical. However, it should be understood that other shapes such as plates, rods, disks, bars, tubes, irregular shapes, and the like are also contemplated by the present invention. The concentration of the particles in the dispersion may vary depending on the desired viscosity of the dispersion and the particular method by which the dispersion is applied to the capacitor element. Typically, however, the particles comprise from about 0.1 to about 10 weight percent of the dispersion, in some embodiments from about 0.4 to about 5 weight percent, and in some embodiments, from about 0.5 to about 4 weight percent.
[0064] The dispersion may also contain one or more binders to further improve the adhesion of the polymer layer and also to increase the stability of the particles in the dispersion.The binder may be of organic nature, such as polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylic acid esters, polyacrylic acid amides, polymethacrylic acid esters, polymethacrylic acid amides, polyacrylonitrile, styrene / acrylic acid esters, vinyl acetate / acrylic acid esters and ethylene / vinyl acetate copolymers, polybutadiene, polyisoprene, polystyrene, polyethers, polyesters, polycarbonates, polyurethanes, polyamides, polyimides, polysulfones, melamine formaldehyde resins, epoxide resins, silicone resins or cellulose.Crosslinking agents may also be used to increase the adhesive capacity of the binder. Such crosslinking agents can include, for example, melamine compounds, masked isocyanates or functional silanes such as 3-glycidoxypropyltrialkoxysilane, tetraethoxysilane, and tetraethoxysilane hydrolysates, or crosslinkable polymers such as polyurethanes, polyacrylates, or polyolefins, which can include subsequent crosslinking.
[0065] Dispersants can also be used to facilitate the ability to apply the layer to the anode. Suitable dispersants include solvents such as aliphatic alcohols (e.g., methanol, ethanol, i-propanol, and butanol), aliphatic ketones (e.g., acetone and methyl ethyl ketone), aliphatic carboxylic acid esters (e.g., ethyl acetate and butyl acetate), aromatic hydrocarbons (e.g., toluene and xylene), aliphatic hydrocarbons (e.g., hexane, heptane, and cyclohexane), chlorinated hydrocarbons (e.g., dichloromethane and dichloroethane), aliphatic nitriles (e.g., acetonitrile), aliphatic sulfoxides and sulfones (e.g., dimethyl sulfoxide and sulfolane), aliphatic carboxylic acid amides (e.g., methylacetamide, dimethylacetamide, and dimethylformamide), aliphatic and araliphatic ethers (e.g., diethyl ether and anisole), water, and mixtures of any of the above solvents. A particularly suitable dispersant is water.
[0066] In addition to those mentioned above, other components may also be used in the dispersion, for example, from about 10 nanometers to about 100 micrometers, in some embodiments, from about 50 nanometers to about 50 micrometers, in some embodiments, about 100 nanometers. Conventional fillers having dimensions of up to about 30 micrometers can be used. Examples of such fillers include calcium carbonate, silicates, silica, calcium or barium sulfate, aluminum hydroxide, glass fibers or glass spheres, wood flour, cellulose powder, carbon black, conductive polymers, etc. The fillers can be introduced into the dispersion in powder form, but can also be present in other forms, such as fibers.
[0067] Surface active substances such as ionic or non-ionic surfactants can also be used in the dispersion. In addition, adhesives such as organofunctional silanes or their hydrolysates, for example, 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane can be used. The dispersion can also contain ether group-containing compounds (e.g., tetrahydrofuran), lactone group-containing compounds (e.g., γ-butyrolactone or γ-valerolactone), amide or lactam group-containing compounds (e.g., caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylformamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone (NMP), N-octylpyrrolidone, or pyrrolidone), sulfones and Additives that increase conductivity may also be included, such as sulfoxides (e.g., sulfolane (tetramethylene sulfone) or dimethyl sulfoxide (DMSO)), sugars or sugar derivatives (e.g., sucrose, glucose, fructose, or lactose), sugar alcohols (e.g., sorbitol or mannitol), furan derivatives (e.g., 2-furan carboxylic acid or 3-furan carboxylic acid), alcohols (e.g., ethylene glycol, glycerol, di- or triethylene glycol).
[0068] The dispersion can be applied using a variety of known techniques, such as by spin coating, impregnation, pouring, drop application, injection, spraying, doctor blade application, brush application, printing (e.g., inkjet, screen, or pad printing), or immersion. The viscosity of the dispersion is typically from about 0.1 to about 100,000 mPa·s (100 s -1 In some embodiments, the shear rate is about 1 to about 10,000 mPa·sec, in some embodiments, about 10 to about 1,500 mPa·sec, and in some embodiments, about 100 to about 1000 mPa·sec.
[0069] If desired, hydroxyl-functional nonionic polymers can also be used in one or more outer layers of the solid electrolyte. The term "hydroxyl-functional" generally means that the compound contains at least one hydroxyl functional group or is capable of having such functionality in the presence of a solvent. Without intending to be limited by theory, it is believed that the use of hydroxyl-functional polymers having a certain molecular weight can minimize the possibility of chemical decomposition at high voltages. For example, the molecular weight of the hydroxyl-functional polymer can be about 100 to 10,000 grams / mole, in some embodiments about 200 to 2,000 grams / mole, in some embodiments about 300 to about 1,200 grams / mole, and in some embodiments about 400 to about 800 grams / mole.
[0070] Generally, any of a variety of hydroxy-functional nonionic polymers can be used for this purpose. For example, in one embodiment, the hydroxy-functional polymer is a polyalkylene ether. Polyalkylene ethers can include polyalkylene glycols (e.g., polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyepichlorohydrin, etc.), polyoxetanes, polyphenylene ethers, polyetherketones, etc. Polyalkylene ethers are typically primarily linear nonionic polymers with terminal hydroxy groups. Polyethylene glycol, polypropylene glycol, and polytetramethylene glycol (polytetrahydrofuran) are preferred. ) are particularly suitable, which are prepared by polyaddition of ethylene oxide, propylene oxide or tetrahydrofuran to water. Polyalkylene ethers can be prepared from diols or polyols by polycondensation reactions. The diol component can be selected in particular from saturated or unsaturated, branched or unbranched aliphatic or aromatic dihydroxy compounds containing 5 to 36 carbon atoms, such as pentane-1,5-diol, hexane-1,6-diol, neopentyl glycol, bis-(hydroxymethyl)-cyclohexane, bisphenol A, dimer diols, hydrogenated dimer diols or even mixtures of the abovementioned diols. Furthermore, polyhydric alcohols, such as, for example, glycerol, di- and polyglycerol, trimethylolpropane, pentaerythritol or sorbitol, can also be used in the polymerization reaction.
[0071] In addition to those mentioned above, other hydroxy-functional nonionic polymers can be used in the present invention. Some examples of such polymers include, for example, ethoxylated alkylphenols; ethoxylated or propoxylated C6-C 24 Aliphatic alcohols; general formula: CH3-(CH2) 10-16 -(O-C2H4) 1-25 Polyoxyethylene glycol alkyl ethers having -OH (e.g., octaethylene glycol monododecyl ether and pentaethylene glycol monododecyl ether); general formula: CH3-(CH2) 10-16 -(O-C3H6) 1-25 Polyoxypropylene glycol alkyl ethers having the general formula: CH 17 -(C6H4)-(O-C2H4) 1-25 Polyoxyethylene glycol octylphenol ether having -OH (e.g. Triton® X-100); 19 -(C6H4)-(O-C2H4) 1-25 Polyoxyethylene glycol alkylphenol ethers with -OH (e.g. nonoxynol-9); C8-C 24Polyoxyethylene glycol esters of fatty acids, such as polyoxyethylene glycol sorbitan alkyl esters (e.g., polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (20) sorbitan monopalmitate, polyoxyethylene (20) sorbitan monostearate, polyoxyethylene (20) sorbitan monooleate, PEG-20 methyl glucose distearate, PEG-20 methyl glucose sesquistearate, PEG-80 castor oil, and PEG-20 castor oil, PEG-3 castor oil, PEG-600 dioleate, and PEG-400 dioleate), and polyoxyethylene glycerol alkyl esters (e.g., polyoxyethylene-23 glycerol laurate, and polyoxyethylene-20 glycerol stearate); C8 to C9 24 Polyoxyethylene glycol ethers of fatty acids (e.g., polyoxyethylene-10 cetyl ether, polyoxyethylene-10 stearyl ether, polyoxyethylene-20 cetyl ether, polyoxyethylene-10 oleyl ether, polyoxyethylene-20 oleyl ether, polyoxyethylene-20 isohexadecyl ether, polyoxyethylene-15 tridecyl ether, and polyoxyethylene-6 tridecyl ether); block copolymers of polyethylene glycol and polypropylene glycol (e.g., Poloxamers); and the like, and mixtures thereof.
[0072] The hydroxy-functional non-ionic polymer can be incorporated into the outer layer in a variety of different ways. For example, in some embodiments, the non-ionic polymer can simply be incorporated into a dispersion of the exogenous conductive polymer. In such embodiments, the concentration of the non-ionic polymer in the layer can be from about 1% to about 50% by weight, in some embodiments, from about 5% to about 40% by weight, and in some embodiments, from about 10% to about 30% by weight. However, in other embodiments, the non-ionic polymer can be applied after the initial outer layer or layers are formed. In such embodiments, the technique used to apply the non-ionic polymer can vary. For example, the non-ionic polymer can be applied in the form of a liquid solution using a variety of methods, such as impregnation, dipping, pouring, dripping, injecting, spraying, spreading, painting, or printing, e.g., inkjet or screen printing. Solvents known to those skilled in the art, such as water, alcohol, or mixtures thereof, can be used in the solution. The concentration of the nonionic polymer in such solutions typically ranges from about 5% to about 95% by weight of the solution, in some embodiments from about 10% to about 70% by weight, and in some embodiments, from about 15% to about 50% by weight. If desired, such solutions can be entirely free of conductive polymer. For example, the conductive polymer can constitute up to about 2% by weight of the solution, in some embodiments up to about 1% by weight, and in some embodiments up to about 0.5% by weight.
[0073] E. Outer polymer coating If desired, an external polymer coating may also be applied to the anode disposed on the solid electrolyte. If used, the external polymer coating typically includes one or more layers formed from conductive polymer particles (e.g., formed from an extrinsic conductive polymer) as described above. The external coating may further penetrate into the edge regions of the capacitor body to increase adhesion to the dielectric and provide a more mechanically robust part, which may reduce equivalent series resistance and leakage current. Generally, since it is intended to improve edge coverage rather than impregnate the interior of the anode body, the particles used in the external coating typically have larger dimensions than those used in the optional particles used in the solid electrolyte (e.g., in one or more outer layers). For example, the ratio of the average size of the particles used in the external polymer coating to the average size of the particles used in the solid electrolyte is typically about 1.5 to about 30, in some embodiments about 2 to about 20, and in some embodiments about 5 to about 15. For example, the particles used in the outer coating may have an average size of from about 50 to about 800 nanometers, in some embodiments, from about 80 to about 600 nanometers, and in some embodiments, from about 100 to about 500 nanometers.
[0074] Optionally, a crosslinking agent can be used in the outer polymer coating to further increase adhesion to the solid electrolyte. Typically, the crosslinking agent is applied before applying the dispersion used in the outer coating. Suitable crosslinking agents are described, for example, in U.S. Patent Publication No. 2007 / 0064376 to Merker et al., and include, for example, amines (e.g., diamines, triamines, oligomeric amines, polyamines, etc.); salts or compounds of polyvalent metal cations, such as Mg, Al, Ca, Fe, Cr, Mn, Ba, Ti, Co, Ni, Cu, Ru, Ce, or Zn, phosphonium compounds, sulfonium compounds, etc. Particularly suitable examples include, for example, 1,4-diaminocyclohexane, 1,4-bis(aminomethyl)cyclohexane, ethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, N,N-dimethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,4-butanediamine, and the like, as well as mixtures thereof.
[0075] The crosslinker is typically applied from a solution or dispersion, the pH of which is 1-10, in some embodiments 2-7, and in some embodiments 3-6, determined at 25° C. An acidic compound may be used to help achieve the desired pH level. Examples of solvents or dispersants for the crosslinker include water, or organic solvents, such as alcohols, ketones, carboxylic acid esters, and the like. The crosslinker may be applied to the capacitor body by any known process, such as spin coating, impregnation, casting, drop application, spray application, vapor deposition, sputtering, sublimation, knife coating, painting, or printing, such as inkjet, screen, or pad printing. Once applied, the crosslinker may be dried before applying the polymer dispersion. This process may then be repeated until the desired thickness is achieved. For example, the total thickness of the entire outer polymer coating, including the layers of crosslinker and dispersion, may range from about 1 to about 50 μm, in some embodiments from about 2 to about 40 μm, and in some embodiments from about 5 to about 20 μm.
[0076] F. Cathode Coating If desired, the capacitor element may also employ a cathode coating disposed over the solid electrolyte and the outer polymer coating. The cathode coating may include a metal particle layer including a multiplicity of conductive metal particles dispersed within a polymer matrix. The particles typically comprise from about 50% to about 99% by weight of the layer, in some embodiments from about 60% to about 98% by weight, and in some embodiments from about 70% to about 95% by weight, while the polymer matrix typically comprises from about 1% to about 50% by weight, in some embodiments from about 2% to about 40% by weight, and in some embodiments from about 5% to about 30% by weight of the layer.
[0077] The conductive metal particles can be formed from a variety of different metals, such as copper, nickel, silver, nickel, zinc, tin, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, and the like, as well as alloys thereof. Silver is a particularly suitable conductive metal for use in such layers. The metal particles often have relatively small dimensions, such as an average diameter of about 0.01 to about 50 micrometers, in some embodiments about 0.1 to about 40 micrometers, and in some embodiments about 1 to about 30 micrometers. It should be understood that, although typically only one layer of metal particles is used, multiple layers can be used if desired. The total thickness of such one or more layers is in the range of about 1 μm to about 500 μm, in some embodiments about 5 μm to about 200 μm, and in some embodiments about 10 μm to about 100 μm.
[0078] The polymer matrix typically comprises a polymer which may be thermoplastic or thermosetting in nature. However, typically the polymer is selected to contain a relatively small amount of polar groups which can act as a barrier to electromigration of silver ions and also minimize the degree of water adsorption in the cathode coating. In this regard, the inventors have found that vinyl acetal polymers such as polyvinyl butyral, polyvinyl formal, and the like are particularly suitable for this purpose. For example, polyvinyl butyral can be formed by reacting polyvinyl alcohol with an aldehyde (e.g., butyraldehyde). Because this reaction is usually not complete, polyvinyl butyral generally has a residual hydroxyl content. However, by minimizing this content, the polymer can have a lower degree of strongly polar groups which would otherwise cause a high degree of moisture adsorption and migration of silver ions. For example, the residual hydroxyl content in polyvinyl acetal can be about 35 mol % or less, in some embodiments about 30 mol % or less, and in some embodiments, about 10 mol % to about 25 mol %. One commercially available example of such a polymer is available from Sekisui Chemical Co., Ltd. under the designation "BH-S" (polyvinyl butyral).
[0079] To form the cathode coating, a conductive paste is typically applied to the capacitor over the solid electrolyte. One or more organic solvents are typically used in the paste. Typically, the organic solvents include glycols (e.g., propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiglycol, and dipropylene glycol); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, and isopropyl glycol ether); ethers (e.g., diethyl ether and tetrahydrofuran); alcohols (e.g., benzyl alcohol, methanol, ethanol, n-propanol, iso-propanol, and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, and methoxypropyl acetate); amides (e.g., dimethylformamide ... A variety of different organic solvents can be used, such as: dimethylacetamide, dimethylcapryl / capric fatty acid amides, and N-alkylpyrrolidones; nitriles (e.g., acetonitrile, propiononitrile, butyronitrile, and benzonitrile); sulfoxides or sulfones (e.g., dimethylsulfoxide (DMSO) and sulfolane); and the like, as well as mixtures thereof. The organic solvent or organic solvents typically comprise from about 10% to about 70% by weight, in some embodiments from about 20% to about 65% by weight, and in some embodiments from about 30% to about 60% by weight of the paste. Typically, the metal particles comprise from about 10% to about 60% by weight, in some embodiments from about 20% to about 45% by weight, and in some embodiments from about 25% to about 40% by weight of the paste, and the resinous matrix comprises from about 0.1% to about 20% by weight, in some embodiments from about 0.2% to about 10% by weight, and in some embodiments from about 0.5% to about 8% by weight of the paste.
[0080] The paste may have a relatively low viscosity, which allows it to be easily handled and applied to the capacitor element. The viscosity may range from about 50 to about 3,000 centipoise, in some embodiments from 100 to about 2,000 centipoise, and in some embodiments from about 200 to about 1,000 centipoise, as measured, for example, using a Brookfield DV-1 viscometer (cone plate) or the like, operating at a speed of 10 rpm and a temperature of 25° C. If desired, thickeners or other viscosity modifiers can be used in the paste to increase or decrease the viscosity. Additionally, the paste may be applied at a relatively thin thickness and still achieve the desired properties. For example, the paste may have a thickness of about 0.01 to about 50 micrometers, in some embodiments from about 0.5 to about 30 micrometers, and in some embodiments from about 1 to about 25 micrometers. Once applied, the metal paste may be optionally dried to remove some components, such as the organic solvent. For example, drying can be carried out at a temperature of about 20°C to about 150°C, in some embodiments, about 50°C to about 140°C, and in some embodiments, about 80°C to about 130°C.
[0081] G. Other Components: If desired, other layers known in the art may also be included in the capacitor. For example, in some embodiments, a carbon layer (e.g., graphite) may be disposed between the solid electrolyte and the silver layer to help further limit contact between the silver layer and the solid electrolyte. Additionally, a precoat layer disposed over the dielectric and comprising an organometallic compound may also be used.
[0082] II. Termination: Once formed, the capacitor element may be provided with terminations, particularly for use in surface mount applications. For example, the capacitor may include an anode termination to which the anode lead of the capacitor element is electrically connected, and a cathode termination to which the cathode of the capacitor element is electrically connected. Any conductive material may be used to form the terminations, such as conductive metals (e.g., copper, nickel, silver, nickel, zinc, tin, palladium, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, and alloys thereof). Particularly suitable conductive metals include, for example, copper, copper alloys (e.g., copper-zirconium, copper-magnesium, copper-zinc, or copper-iron), nickel, and nickel alloys (e.g., nickel-iron). The thickness of the terminations is generally selected to minimize the thickness of the capacitor. For example, the thickness of the terminations may range from about 0.05 to about 1 millimeter, in some embodiments, from about 0.05 to about 0.5 millimeters, and from about 0.07 to about 0.2 millimeters. One exemplary conductive material is a metal plate of copper-iron alloy available from Wieland (Germany). If desired, the surfaces of the terminations may be polished to ensure that the final component can be mounted to a circuit board, as is known in the art. It can be electroplated with nickel, silver, gold, tin, etc. In one particular embodiment, both surfaces of the termination are plated with nickel and silver flash, respectively, while the mounting surface is also plated with a tin solder layer.
[0083] The terminations can be connected to the capacitor elements using any technique known in the art. For example, in one embodiment, a lead frame can be provided that defines a cathode termination and an anode termination. To attach the electrolytic capacitor elements to the lead frame, a conductive adhesive can first be applied to the surface of the cathode termination. The conductive adhesive can include, for example, conductive metal particles contained in a resin composition. The metal particles can be silver, copper, gold, platinum, nickel, zinc, bismuth, etc. The resin composition can include a thermosetting resin (e.g., an epoxy resin), a hardener (e.g., an acid anhydride), and a coupling agent (e.g., a silane coupling agent). Suitable conductive adhesives are described in U.S. Patent Application Publication No. 2006 / 0038304 to Osako et al. The conductive adhesive can be applied to the cathode termination using any of a variety of techniques. For example, printing techniques can be used for their practical and cost-saving benefits. The anode lead can also be electrically connected to the anode termination using any technique known in the art, such as mechanical welding, laser welding, conductive adhesives, etc. Once the anode lead has been electrically connected to the anode termination, the conductive adhesive may then be cured to ensure proper adhesion of the electrolytic capacitor element to the cathode termination.
[0084] III. Housing The capacitor element can be incorporated into the housing in a variety of ways. For example, in some embodiments, the capacitor element can be housed in a case, which can then be filled with a resin material, such as a thermosetting resin (e.g., an epoxy resin), which can be cured to form a hardened housing. The resin material can surround and encapsulate the capacitor element such that at least a portion of the anode and cathode terminations are exposed for mounting on a circuit board. When encapsulated in this manner, the capacitor element and the resin material form an integral capacitor.
[0085] Of course, in other embodiments, it may be desirable to house the capacitor elements separately and in isolation within the housing. In this manner, the atmosphere of the housing can be selectively controlled to be dry, thereby limiting the amount of moisture that can contact the capacitor elements. For example, the moisture content of air (expressed as relative humidity) may be about 10% or less, in some embodiments about 5% or less, in some embodiments about 3% or less, and in some embodiments about 0.001 to about 1%. For example, the atmosphere may be gaseous and include at least one inert gas, such as nitrogen, helium, argon, xenon, neon, krypton, radon, and the like, as well as mixtures thereof. Typically, the inert gas constitutes a majority of the atmosphere within the housing, for example, about 50% to 100% by weight, in some embodiments about 75% to 100% by weight, and in some embodiments about 90% to about 99% by weight of the atmosphere. If desired, relatively small amounts of non-inert gases, such as carbon dioxide, oxygen, water vapor, and the like, may also be used. However, in such cases, the non-inert gas typically comprises no more than 15% by weight of the atmosphere within the housing, in some embodiments no more than 10% by weight, in some embodiments no more than about 5% by weight, in some embodiments no more than about 1% by weight, and in some embodiments from about 0.01% to about 1% by weight.
[0086] Any of a variety of different materials may be used to form the housing, such as metal, plastic, ceramic, etc. For example, in one embodiment, the housing is made of any of tantalum, niobium, aluminum, nickel, hafnium, titanium, copper, silver, steel (e.g., stainless steel), alloys thereof (e.g., conductive oxides), composites thereof (e.g., conductive oxides), and the like. In some embodiments, the housing may include one or more layers of a metal, such as a ceramic material, such as aluminum nitride, aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, glass, and the like, as well as combinations thereof.
[0087] The housing may have any desired shape, such as cylindrical, D-shaped, rectangular, triangular, prismatic, etc. For example, referring to FIG. 1, one embodiment of a capacitor 100 is shown that includes a housing 122 and a capacitor element 120. In this particular embodiment, the housing 122 is generally rectangular. Typically, the housing and the capacitor element have the same or similar shapes so that the capacitor element can be easily accommodated within the internal cavity. For example, in the embodiment shown, both the capacitor element 120 and the housing 122 have a generally rectangular shape.
[0088] If desired, the capacitors of the present invention can exhibit a relatively high volumetric efficiency. To facilitate such high efficiency, the capacitor element typically occupies a substantial portion of the volume of the interior cavity of the housing. For example, the capacitor element can occupy about 30% by volume or more, in some embodiments about 50% by volume or more, in some embodiments about 60% by volume or more, in some embodiments about 70% by volume or more, in some embodiments about 80% to about 98% by volume, and in some embodiments about 85% to about 97% by volume of the interior cavity of the housing. To this end, the difference between the dimensions of the capacitor element and the dimensions of the interior cavity defined by the housing is typically relatively small.
[0089] For example, referring to FIG. 1, the capacitor element 120 may have a length (excluding the length of the anode lead 6) that is relatively similar to the length of the interior cavity 126 defined by the housing 122. For example, the ratio of the length of the anode to the length of the interior cavity may range from about 0.40 to 1.00, in some embodiments from about 0.50 to about 0.99, in some embodiments from about 0.60 to about 0.99, and in some embodiments from about 0.70 to about 0.98. The capacitor element 120 may have a length of about 5 to about 10 millimeters, and the interior cavity 126 may have a length of about 6 to about 15 millimeters. Similarly, the ratio of the height (in the z-direction) of the capacitor element 120 to the height of the interior cavity 126 may range from about 0.40 to 1.00, in some embodiments from about 0.50 to about 0.99, in some embodiments from about 0.60 to about 0.99, and in some embodiments from about 0.70 to about 0.98. The ratio of the width (in the x-direction) of capacitor element 120 to the width of internal cavity 126 may also range from about 0.50 to 1.00, in some embodiments from about 0.60 to about 0.99, in some embodiments from about 0.70 to about 0.99, in some embodiments from about 0.80 to about 0.98, and in some embodiments from about 0.85 to about 0.95. For example, the width of capacitor element 120 may be from about 2 to about 7 millimeters, the width of internal cavity 126 may be from about 3 to about 10 millimeters, the height of capacitor element 120 may be from about 0.5 to about 2 millimeters, and the width of internal cavity 126 may be from about 0.7 to about 6 millimeters.
[0090] Although by no means required, the capacitor element can be attached to the housing such that anode and cathode terminations are formed on the exterior of the housing for subsequent incorporation into the circuit. The particular configuration of the terminations can depend on the intended application. For example, in one embodiment, the capacitor can be formed to be surface mountable and yet mechanically robust. For example, the anode lead can be electrically connected to exterior surface mountable anode and cathode terminations (e.g., pads, sheets, plates, frames, etc.). Such terminations can extend through the housing to connect with the capacitor. The thickness or height of the terminations is generally selected to minimize the thickness of the capacitor. For example, the thickness of the terminations can be from about 0.05 to about 1 millimeter, and in some embodiments, about 0. The thickness may range from .05 to about 0.5 millimeters, and from about 0.1 to about 0.2 millimeters. If desired, the surfaces of the terminations may be electroplated with nickel, silver, gold, tin, or the like, as known in the art, to ensure that the final component will be mountable to a circuit board. In one particular embodiment, one or more of the terminations are each deposited with a nickel and silver flash, and the mounting surfaces are also plated with a tin solder layer. In other embodiments, one or more of the terminations have a thin outer metal layer (e.g., gold) deposited on a base metal layer (e.g., a copper alloy) to further increase electrical conductivity.
[0091] In some embodiments, a connecting member may be used within the internal cavity of the housing to facilitate connection to the terminations in a mechanically stable configuration. For example, referring again to FIG. 1, the capacitor 100 may include a connecting member 162 formed from a first portion 167 and a second portion 165. The connecting member 162 may be formed from the same conductive material as the external terminations. The first portion 167 and the second portion 165 may be integral or may be separate pieces connected either directly or via a further conductive member (e.g., metal). In the embodiment shown, the second portion 165 is provided in a plane generally parallel to the lateral direction (e.g., y-direction) in which the leads 6 extend. The first portion 167 is "upright" in the sense that it is provided in a plane generally perpendicular to the lateral direction in which the leads 6 extend. In this manner, the first portion 167 may limit horizontal movement of the leads 6 to increase surface contact and mechanical stability during use. If desired, an insulating material 7 (e.g., a Teflon™ washer) may be used around the leads 6.
[0092] First portion 167 may have a mounting region (not shown) that is connected to anode lead 6. Such region may have a "U-shape" to further increase surface contact and mechanical stability of lead 6. Connection of such region to lead 6 may be accomplished using any of a variety of known techniques, such as welding, laser welding, conductive adhesives, and the like. For example, in one particular embodiment, this region is laser welded to anode lead 6. However, regardless of the technique selected, first portion 167 may hold anode lead 6 in a substantially horizontal orientation to further increase dimensional stability of capacitor 100.
[0093] 1, an embodiment of the present invention is shown in which the connection member 162 and the capacitor element 120 are connected to the housing 122 through anode and cathode terminations (127 and 129, respectively). More specifically, the housing 122 in this embodiment includes an exterior wall 123 and two opposing side walls 124 defining a cavity 126 therebetween for receiving the capacitor element 120. The exterior wall 123 and the side walls 124 may be formed from one or more layers of metal, plastic, or ceramic material as described above. In this particular embodiment, the anode termination 127 includes a first region 127a disposed within the housing 122 and electrically connected to the connection member 162, and a second region 127b disposed outside the housing 122 and providing a mounting surface 201. Additionally, cathode termination 129 includes a first region 129a disposed within housing 122 and electrically connected to the solid electrolyte of capacitor element 120, and a second region 129b disposed outside housing 122 and providing mounting surface 203. It should be understood that portions of such regions need not be entirely disposed within or outside the housing.
[0094] In the embodiment shown, conductive trace 127c extends within the housing's exterior wall 123 to connect first region 127a and second region 127b. Similarly, conductive trace 129c extends within the housing's exterior wall 123 to connect first region 127a and second region 127b. The conductive traces and / or termination regions may be separate or integral. In addition to extending through the housing's exterior wall, the traces may be located elsewhere, such as on the outside of the exterior wall. Of course, the present invention contemplates any suitable method for forming a desired termination. The present invention is by no means limited to the use of conductive traces for purposes of illustration.
[0095] Regardless of the particular configuration used, the connection of terminations 127 and 129 to capacitor element 120 may be made using any known technique, such as welding, laser welding, conductive adhesives, etc. For example, in one particular embodiment, conductive adhesive 131 is used to connect second portion 165 of connecting member 162 to anode termination 127. Additionally, conductive adhesive 133 is used to connect the cathode of capacitor element 120 to cathode termination 129.
[0096] In some cases, the polymeric constraining member may be disposed in contact with one or more surfaces of the capacitor element, such as the rear surface, the front surface, the top surface, the bottom surface, one or more side surfaces, or any combination thereof. The polymeric constraining member may reduce the likelihood of the capacitor element delaminating from the housing. In this regard, the polymeric constraining member may have some strength that allows it to hold the capacitor element in a relatively fixed position even when subjected to vibration forces, but is not so tough that it will crack. For example, the constraining member may have a tensile strength, measured at a temperature of about 25° C., of about 1 to about 150 megapascals (MPa), in some embodiments, about 2 to about 100 MPa, in some embodiments, about 10 to about 80 MPa, and in some embodiments, about 20 to about 70 MPa. It is typically desirable that the constraining member is not electrically conductive. For example, referring again to FIG. 1, an embodiment is shown in which a single polymeric constraining member 197 is disposed in contact with the top surface 181 and the rear surface 177 of the capacitor element 120. Although a single constraining member is shown in FIG. 1, it should be understood that separate constraining members may be used to achieve the same function. Indeed, more generally, any number of polymeric constraining members can be used to contact any desired surface of the capacitor element. When multiple constraining members are used, they can be in contact with each other or can be held physically separate. For example, in one embodiment, a second polymeric constraining member (not shown) can be used that contacts the top surface 181 and front surface 179 of the capacitor element 120. The first polymeric constraining member 197 and the second polymeric constraining member (not shown) can be in contact with each other or not. In yet other embodiments, the polymeric constraining member can be in contact with the bottom surface 183 and / or one or more side surfaces of the capacitor element 120 in addition to or instead of other surfaces.
[0097] Regardless of how it is applied, it is typically desirable for the polymeric constraining member to also be in contact with at least one surface of the housing to help further mechanically stabilize the capacitor element against potential delamination. For example, the constraining member can be in contact with the interior surface of one or more side walls, exterior walls, lid, etc. For example, in FIG. 1, the polymeric constraining member 197 is in contact with the interior surface 107 of the side wall 124 and the interior surface 109 of the exterior wall 123. Although in contact with the housing, it is desirable for at least a portion of the cavity defined by the housing to remain unoccupied to allow inert gas to flow through the cavity to limit contact of the solid electrolyte with oxygen. For example, at least about 5% of the cavity volume, and in some embodiments about 10% to about 50% of the cavity volume, typically remains unoccupied by the capacitor element and the polymeric constraining member.
[0098] Once connected in the desired configuration, the resulting package is hermetically sealed as described above. For example, referring again to FIG. 1, the housing 122 may also include a lid 125 that is disposed on top of the sidewall 124 after the capacitor element 120 and polymeric restraining member 197 are disposed within the housing 122. The lid 125 may be formed from a ceramic, a metal (e.g., iron, copper, nickel, cobalt, etc., and alloys thereof), a plastic, or the like. If desired, a sealing member 187 may be disposed between the lid 125 and the sidewall 124 to help provide a good seal. For example, in one embodiment, the sealing member may include a glass-to-metal seal, a Kovar® ring (Goodfellow Camridge, Ltd.), or the like. The height of the sidewall 124 is generally determined by the thickness of the lid 125. The height is such that the lid 125 does not contact any surface of the capacitor element 120 to avoid contamination of the capacitor element. The polymeric restraining member 197 may or may not be in contact with the lid 125. Once in the desired location, the lid 125 is hermetically sealed to the sidewall 124 using known techniques such as welding (e.g., resistance welding, laser welding, etc.), soldering, etc. The hermetic sealing is typically performed in the presence of an inert gas, such as those described above, so that the resulting assembly is substantially free of reactive gases such as oxygen or water vapor.
[0099] It should be understood that the described embodiment is merely exemplary, and various other configurations for hermetically sealing the capacitor element within the housing can be used in the present invention. For example, referring to FIG. 2, another embodiment of a capacitor 200 is shown using a housing 222 including an outer wall 123 and a lid 225, forming a cavity 126 therebetween for receiving the capacitor element 120 and the polymeric restraining member 197. The lid 225 includes an outer wall 223 integral with at least one side wall 224. For example, in the embodiment shown, two opposing side walls 224 are shown in cross section. The outer walls 223 and 123 both extend in a lateral direction (y direction) and are generally parallel to each other and to the lateral direction of the anode lead 6. The side wall 224 extends from the outer wall 223 in a longitudinal direction that is generally perpendicular to the outer wall 123. The distal end 500 of the lid 225 is defined by the outer wall 223 and the proximal end 501 is defined by the lip 253 of the side wall 224 .
[0100] The lip 253 extends laterally from the sidewall 224, which may be generally parallel to the lateral direction of the outer wall 123. The angle between the sidewall 224 and the lip 253 may vary, but is typically between about 60° and about 120°, in some embodiments between about 70° and about 110°, and in some embodiments, between about 80° and about 100° (e.g., about 90°). The lip 253 also defines a peripheral edge 251, which may be generally perpendicular to the lateral direction in which the lip 253 and the outer wall 123 extend. The peripheral edge 251 is located beyond the periphery of the sidewall 224 and may be generally flush with the edge 151 of the outer wall 123. The lip 253 may be sealed to the outer wall 123 using any known technique, such as welding (e.g., resistance or laser), soldering, adhesives, etc. For example, in the embodiment shown, a sealing member 287 (glass-to-metal seal, Kovar® ring, etc.) is used between the components to facilitate bonding therebetween. In any case, the use of such a lip allows for a more stable connection between the components and can improve the sealing and mechanical stability of the capacitor.
[0101] Still other possible housing structures can be used in the present invention. For example, FIG. 3 shows a capacitor 300 having a housing structure similar to that of FIG. 2, except that terminal pins 327b and 329b are used as external terminations for the anode and cathode, respectively. More specifically, terminal pin 327a extends through a trace 327c formed in the outer wall 323 and is connected to the anode lead 6 using known techniques (e.g., welding). A further section 327a can be used to secure pin 327b. Furthermore, terminal pin 329b extends through a trace 329c formed in the outer wall 323 and is connected to the cathode by the conductive adhesive 133 described above.
[0102] The embodiment shown in Figures 1-3 is discussed herein with respect to only a single capacitor element. However, it should be understood that multiple capacitor elements may also be hermetically sealed within the housing. The multiple capacitor elements may be attached to the housing using any of a variety of different techniques. For example, with reference to Figure 4, one particular embodiment of a capacitor 400 including two capacitor elements is shown and will now be described in more detail. More specifically, capacitor 400 includes a first capacitor element 420a in electrical communication with a second capacitor element 420b. In this embodiment, the capacitor elements are arranged such that their major surfaces are in a horizontal configuration. That is, the major surface of capacitor element 420a, defined by its width (x-direction) and length (y-direction), is substantially parallel to the surface of the capacitor element 420b. The capacitor elements 420a and 420b are disposed adjacent to corresponding major surfaces of the capacitor elements 420b. Thus, these major surfaces are generally coplanar. Alternatively, the capacitor elements can be disposed such that their major surfaces are not coplanar but are perpendicular to one another in a certain direction, such as the z direction or the x direction. Of course, the capacitor elements need not extend in the same direction.
[0103] The capacitor elements 420a and 420b are disposed within a housing 422 that includes an outer wall 423 and side walls 424 and 425 that together define a cavity 426. Although not shown, a lid can be used to cover the tops of the side walls 424 and 425 and seal the assembly 400 as described above. In some cases, a polymeric restraining member can be used to help limit vibration of the capacitor elements. For example, in FIG. 4, separate polymeric restraining members 497a and 497b are disposed adjacent to and in contact with the capacitor elements 420a and 420b, respectively. The polymeric restraining members 497a and 497b can be disposed in a variety of different locations. Furthermore, one of the restraining members can be eliminated or additional restraining members can be used. For example, in some embodiments, it may be desirable to use polymeric restraining members between the capacitor elements to further improve mechanical stability.
[0104] In addition to the capacitor elements, the capacitor also includes an anode termination to which the anode lead of each capacitor element is electrically connected, and a cathode termination to which the cathode of each capacitor element is electrically connected. For example, referring again to FIG. 4, a plurality of capacitor elements are shown connected in parallel to a common cathode termination 429. In this particular embodiment, the cathode termination 429 is first provided in a plane generally parallel to the bottom surface of the capacitor element and may be in electrical contact with a conductive trace (not shown). The capacitor 400 also includes connection members 427 and 527 that are connected to the anode leads (407a and 407b, respectively) of the capacitor elements 420a and 420b. More specifically, the connection member 427 includes an upstanding portion 465 and a planar portion 463 that is connected to the anode termination (not shown). Additionally, the connection member 527 includes an upstanding portion 565 and a planar portion 563 that is connected to the anode termination (not shown). Of course, it should be understood that a wide variety of other types of connection mechanisms may be used. EXAMPLES
[0105] The invention may be better understood with reference to the following examples.
[0106] Test procedure capacitance Capacitance was measured using a Keithley 3330 precision LCZ meter with Kelvin leads, using a DC bias of 2.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency was 120 Hz and the temperature was 23°C ± 2°C.
[0107] Breakdown Voltage Breakdown voltage was measured using a Keithley 2400 SourceMeter at a temperature of 23° C.±2° C. The individual capacitors were determined according to the formula: Current (A) = Nominal Capacitance (F) x dU / dt (where dU / dt represents the voltage gradient, typically set to 10 V / s). The voltage is measured during charging, and the maximum achieved voltage value is recorded as the breakdown voltage when the applied voltage decreases by more than 10%.
[0108] Equivalent Series Resistance (ESR) The equivalent series resistance is a Keithley 3330 precision LCZ with Kelvin leads The meter was used to measure the impedance using a DC bias of 2.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency was 100 kHz and the temperature was 23°C ±2°C.
[0109] Dielectric tangent The dissipation factor may be measured using a Keithley 3330 precision LCZ meter with Kelvin leads, using a DC bias of 2.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency may be 120Hz and the temperature may be 23°C ±2°C. Leakage Current The leakage current may be measured using a leakage tester at a temperature of 23°C ± 2°C and rated voltage after a minimum of 60 seconds.
[0110] Surge Voltage Test Surge voltage testing (10-25 parts) may be performed at a temperature of 85°C ± 3°C and at a voltage of rated voltage multiplied by 1.3 (e.g. 45.5V). The resistance used in the test circuit may be 33 ohms. Each cycle consists of a 30 second application of the surge voltage followed by a 30 second discharge period. The test specimens are dried at 125°C for at least 12 hours prior to testing. Capacitance may be measured after a recovery period for every 1,000 pulse cycles up to 3,000 or 5,000 pulses.
[0111] Dielectric Thickness Dielectric thickness can be measured using a Zeiss Sigma FESEM at magnifications of 20,000x to 50,000x. Samples can be prepared by cutting the finished part at a plane perpendicular to the longest dimension of the finished part. Thickness measurements can be taken at the site of the perpendicular cut through the dielectric layer.
[0112] Example 1 Anode samples were prepared using tantalum powder with 40,000 μFV / g. Each anode sample was embedded with a tantalum wire with a weight of 5.3 g / cm. 3The pellets were pressed to a density of 0.1 mm and sintered at 1380° C. The resulting pellets had dimensions of 5.60×3.65×0.72 mm. The pellets were anodized to 76.0 volts in a water / phosphoric acid electrolyte having a conductivity of 8.6 mS at a temperature of 40° C. to form a dielectric layer. The pellets were anodized again to 130 volts for 10 seconds in a water / boric acid / disodium tetraborate electrolyte having a conductivity of 2.0 mS at a temperature of 30° C. to form a thicker oxide layer deposited on the outside. Once anodized, four precoat layers of an organometallic compound were used, including a solution of (3-aminopropyl)trimethoxysilane in ethanol (1.0%). A conductive polymer coating was formed by immersing the anode in a solution of poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butane-sulfonic acid. Once coated, the parts were dried at 125° C. for 15 min. This process was repeated twice. The parts were then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with 1.1% solids and a viscosity of 20 mPa·s. Once coated, the parts were dried at 125° C. for 15 min. This process was repeated eight times. The parts were then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) with 2.0% solids and a viscosity of 20 mPa·s (Clevios™ K, Heraeus). The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) with a solids content of 2% and a viscosity of 160 mPa·s (Clevios™ K, Heraeus). Once coated, the part was dried at 125°C for 15 minutes. This process was repeated three times. The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) with a solids content of 2% and a viscosity of 160 mPa·s (Clevios™ K, Heraeus). Once coated, the part was dried at 125°C for 15 minutes. This process was repeated fourteen times. The part was then immersed in a graphite dispersion and dried. Finally, the part was immersed in a silver dispersion. In this manner, a number of 47 μF / 35 V capacitor components (450) were fabricated and encapsulated in silica resin.
[0113] Example 2 Capacitors were formed as described in Example 1, except that a different conductive polymer coating was used. The conductive polymer coating was formed by immersing the anode in a solution of poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butane-sulfonic acid. Once coated, the part was dried at 125° C. for 15 minutes. This process was repeated eight times. The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with 2.0% solids and a viscosity of 20 mPa·s. Once coated, the part was dried at 125° C. for 15 minutes. This process was repeated three times. The anode was immersed in an organic solution of polyaniline with dopant and then dried at 150° C. for 30 minutes. A conductive polymer coating was formed by coating the entire composition with sulfonic acid. The entire composition was then immersed in a solution containing sulfonic acid and then dried at 150° C. for 30 minutes. This process was repeated three times. The part was then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) with a solids content of 2% and a viscosity of 160 mPa·s (Clevios™ K. Heraeus). Once coated, the part was dried at 125° C. for 15 minutes. This process was repeated 14 times. The part was then immersed in a graphite dispersion and dried. Finally, the part was immersed in a silver dispersion and dried. A large number of parts (450) of 47 μF / 35 V capacitors were thus produced and encapsulated in silica resin.
[0114] Example 3 Anode samples were prepared using tantalum powder with 40,000 μFV / g. Each anode sample was embedded with a tantalum wire with a weight of 5.3 g / cm. 3The pellets were pressed to a density of 1.0 mm and sintered at 1410° C. The resulting pellets had dimensions of 5.60×3.65×0.80 mm. The pellets were anodized to 76.0 volts in a water / phosphoric acid electrolyte having a conductivity of 8.6 mS at a temperature of 40° C. to form a dielectric layer. The pellets were anodized again to 150 volts for 5 seconds in a water / boric acid / disodium tetraborate electrolyte having a conductivity of 2.0 mS at a temperature of 30° C. to form a thicker oxide layer deposited on the outside. Once anodized, four precoat layers of an organometallic compound were used, including a solution of (3-aminopropyl)trimethoxysilane in ethanol (1.0%). A conductive polymer coating was formed by immersing the anode in a solution of poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-2-butane-sulfonic acid. Once coated, the part was dried at 125 °C for 15 min. This process was repeated twice. The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with 1.1% solids and a viscosity of 20 mPa·s. Once coated, the part was dried at 125 °C for 15 min. This process was repeated eight times. The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with 2.0% solids and a viscosity of 20 mPa·s. The parts were then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with a solids content of 2% and a viscosity of 160 mPa·s. Once coated, the parts were dried at 125° C. for 15 minutes. This process was repeated three times. The parts were then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with a solids content of 2% and a viscosity of 160 mPa·s. Once coated, the parts were dried at 125° C. for 15 minutes. This process was repeated fourteen times. Next, the parts were immersed in a graphite dispersion and dried. Finally, the parts were immersed in a silver dispersion and dried. A large number of parts (450) of 47 μF / 35 V capacitors were thus produced and encapsulated in silica resin.
[0115] Example 4 The capacitor was fabricated in the manner described in Example 3, except that a different conductive polymer coating was used. A conductive polymer coating was formed by immersing the anode in a solution of poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-2-butane-sulfonic acid. Once coated, the part was dried at 125 °C for 15 min. This process was repeated six times. The part was then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with a solids content of 2.0% and a viscosity of 20 mPa·s. Once coated, the part was dried at 125 °C for 15 min. The part was then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) (Clevios™ K, Heraeus) with 2% solids and a viscosity of 160 mPa·s. Once coated, the part was dried at 125° C. for 15 minutes. The process was repeated 14 times. The part was then immersed in a graphite dispersion and allowed to dry. Finally, the part was immersed in a silver dispersion and allowed to dry. A large number of parts (450) of 47 μF / 35 V capacitors were thus produced and encapsulated in silica resin.
[0116] The minimum, average and maximum measured BDV values, as well as the average dielectric thickness, are shown in Table 1 below.
[0117] [Table 1] The median capacitance results within the surge voltage test are shown in Table 2 below.
[0118] [Table 2] These and other modifications and variations of the present invention may be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Moreover, those skilled in the art will recognize that the above description is by way of example only and is not intended to limit the invention as further described in the appended claims.
Claims
1. an anode body comprising tantalum; a dielectric disposed over the anode body; and a solid electrolyte disposed on the dielectric; wherein the solid electrolyte comprises an intrinsically conductive polymer comprising repeating thiophene units, the capacitor exhibits a dielectric strength of about 0.6 volts / nanometer or greater, and further wherein the capacitor exhibits a charge / discharge capacitance after being subjected to 3,000 cycles of a surge voltage and an initial capacitance prior to being subjected to the surge voltage, the ratio of the charge / discharge capacitance to the initial capacitance being about 0.75 to 1.
2. The intrinsically conductive polymer has the following formula (I): 【Chemistry 1】 (In the formula, R is (CH 2 ) a -O-(CH 2 ) b -L (wherein L is a bond or HC([CH 2 ] c H) is; a is 0 to 10; b is 1 to 18; c is 0 to 10; M is an anion; X is a cation.
2. The solid electrolytic capacitor of claim 1 , comprising repeating thiophene units of
3. The intrinsically conductive polymer has the following general formula (III): 【Chemistry 2】 (In the formula, a is 0 to 10; b is 1 to 18; R 5 is an optionally substituted C 1 ~C 6 is a linear or branched alkyl group or a halogen atom; X is a hydrogen atom, an alkali metal, NH(R 1 ) 3 (In the formula, R 1 are each independently a hydrogen atom or an optionally substituted C 1 ~C 6 alkyl group), or HNC 5 H 5 (It is) 2. The solid electrolytic capacitor of claim 1 , comprising a repeating thiophene unit having the formula:
4. 4. The solid electrolytic capacitor according to claim 3, wherein a is 1 and b is 3 or 4.
5. R 5 The solid electrolytic capacitor of claim 3 , wherein is methyl.
6. 4. The solid electrolytic capacitor of claim 3, wherein X is an alkali metal.
7. The thiophene repeating unit is 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl) methoxy]-1-propyl-1-propane-sulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propane-sulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propane-sulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b ]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonic acid sodium salt, -[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl- 1-Propanesulfonic acid potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid ammonium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid triethylammonium, or a combination thereof. The solid electrolytic capacitor of claim 1.
8. 10. The solid electrolytic capacitor of claim 1, wherein the polymer has a specific conductivity of about 20 S / cm or greater.
9. 10. The solid electrolytic capacitor of claim 1, wherein the solid electrolyte comprises at least one inner layer comprising the inherently conductive polymer.
10. 10. The solid electrolytic capacitor of claim 9, wherein the inner layer is generally free of extrinsic conductive polymer.
11. The solid electrolytic capacitor of claim 1 , wherein the solid electrolyte comprises at least an outer layer.
12. 12. The solid electrolytic capacitor of claim 11, wherein the outer layer is formed from particles comprising a polymeric counterion and an extrinsic conductive polymer.
13. 10. The solid electrolytic capacitor of claim 1, further comprising a precoat disposed over the anode body and formed from an organometallic compound.
14. The organometallic compound is represented by the following general formula (II): 【Chemistry 3】 (In the formula, R 1 , R 2 , and R 3 is independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halo, haloalkyl, or hydroxyalkyl; R 4 and R 5 are independently hydrogen, alkyl, independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halo, haloalkyl, hydroxyalkyl, or N, R 4 and R 5 forms a ring structure together with one or more additional atoms; Z is an organic group.
2. The solid electrolytic capacitor of claim 1 , wherein the silane is a monoaminofunctional silane having the formula:
15. 15. The solid electrolytic capacitor of claim 14, wherein the monoaminofunctional silane is a primary amine. Pacita.
16. The solid electrolytic capacitor of claim 15, wherein the primary amine is 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltris(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxypropyltrimethoxysilane, aminopropylsilanetriol, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, or a combination thereof.
17. 15. The solid electrolytic capacitor of claim 14, wherein the monoaminofunctional silane is a secondary amine.
18. The solid electrolytic capacitor of claim 17, wherein the secondary amine is N-butylaminopropyltrimethoxysilane, N-ethylaminoisobutyltrimethoxysilane, n-methylaminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, (phenylaminoethyl)methyl-diethoxysilane, N-phenylaminomethytrimethoxysilane, N-methylaminopropylmethyl-dimethoxysilane, or a combination thereof.
19. The organometallic compound is represented by the following general formula (III): 【Chemistry 4】 (In the formula, R 1 , R 2 , and R 3 is independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halo, haloalkyl, or hydroxyalkyl; Z 1 and Z 2 are independently an organic group.
2. The solid electrolytic capacitor of claim 1 , wherein the diamino-functional silane has the formula:
20. The diamino functional silane is selected from the group consisting of N-(2-aminoethyl)-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(6-aminohexyl)aminomethyltriethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyl 20. The solid electrolytic capacitor according to claim 19, which is selected from the group consisting of trimethoxysilane, (aminoethylaminomethyl)-phenethyltrimethoxysilane, N-3-[(amino(polypropyleneoxy)]-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylamino)-3-isobutyldimethylmethoxysilane, and combinations thereof.
21. 10. The solid electrolytic capacitor of claim 1, further comprising an outer polymer coating disposed over the solid electrolyte, the outer polymer coating comprising conductive polymer particles.
22. 22. The solid electrolytic capacitor of claim 21, wherein the outer polymer coating further comprises a cross-linking agent.
23. 2. The solid electrolytic capacitor of claim 1, wherein the anode body is a sintered pellet.
24. The solid electrolytic capacitor of claim 1 further comprising a housing within which the capacitor element is contained.
25. 10. The solid electrolytic capacitor of claim 1, wherein the capacitor element further comprises a cathode coating comprising a metal particle layer disposed on the solid electrolyte, the metal particle layer comprising a plurality of conductive metal particles.
26. 10. The solid electrolytic capacitor of claim 1, exhibiting a breakdown voltage of about 55 volts or greater.
27. 10. The solid electrolytic capacitor of claim 1, wherein the dielectric has a thickness of about 60 nanometers or greater.